Free fatty acids reduction in waste cooking oil by Rhodosporidium toruloides and simultaneous carotenoids, lipids, and pal enzyme production in a two-phase culture system - Lee, Jaslyn Jie Lin (2022)
Waste cooking oil (WCO) is a problematic waste product that contains free fatty acids (FFAs), preventing it from being valorized easily as biodiesel and poses an environmental hazard if incorrectly disposed. The use of WCO as a carbon source for Rhodosporidium toruloides (R. toruloides) using a two-phase culture system is developed. The normal growth of R. toruloides when cultured in WCO (OD600 52) reveals its ability to use a hydrophobic substrate as the carbon source compared to glucose (OD600 51.9). Interestingly, the extracellular lipase activity when R. toruloides is grown on WCO is 14.4 U mL−1 compared to when grown on glucose (2.4 U mL−1). Additionally, FFA levels in WCO are reduced from 2% to 0.2% at end of fermentation, suggesting that R. toruloides can consume FFA. Furthermore, higher yield of beneficial products: β-carotene (4.57 µg mL−1), torularhodin (4.2 µg mL−1), fatty acids (1 mg mL−1), and phenylalanine ammonia-lyase (PAL) enzyme (0.12 µmol mg−1) are produced when WCO is the carbon source, compared to glucose (4.1 µg mL−1 β-carotene, 3.0 µg mL−1 torularhodin, 1 mg mL−1 of fatty acids, and 0.096 µmol mg−1 PAL enzyme). This is a first study that shows R. toruloides can grow on hydrophobic carbon source.